Dependency disconnection and mechanism ((disengagement)) - سعد, فيصل (Tishreen University Journal- Arts and Humanities Sciences Series, 2021)
The information, communication and transportation revolution that humanity is witnessing today, for at least four decades, has led to what has come to be known as the one "global village". And in light of a global capitalist system of identity and nationality By virtue of the polarizing nature of this global system (polarized between subordinate countries and subordinate countries of centers), dependency, as a phenomenon with internal and external dimensions, is its most present and dangerous phenomenon. As such, it is a direct expression of the backwardness of the dependent countries; It is a double backwardness that has always been, at the same time, a technical and structural backwardness, that is, in the field of productive forces as well as in the field of production relations In this way, the cessation of underdevelopment as a gateway to development requires, of necessity, objectivity, the severance of dependency. There are many mechanisms related to this process, perhaps the most prominent and important of which is the "disengagement" mechanism. With the need to emphasize here, that this mechanism does not mean "Autarchism", in any way, as long as the challenge of underdevelopment in the first field requires technological linkage with the centers of the global system through the mechanisms of the capitalist market, prevailing there and on the global level. Which means, logically, that disengagement is control of the association itself as a necessary component of it; This will soon lead to severing the structural links of dependency As a result, cutting dependence on the "disengagement and engagement" mechanism, in this way, requires, in an organic manner, the work of the "market and planning" mechanism; This is because "disengagement" presupposes planning, just as "engagement" presupposes the market, both together and on the same level